Bone density in elite judoists and effects of weight cycling on bone metabolic balance - Prouteau, S.; Pelle, A.; Collomp, K.; Benhamou, L.; Courteix, D. (Medicine & Science in Sports & Exercise, 2006)
Purpose: Weight cycling has been shown to exert negative effects on bone metabolism and bone mass, whereas weight-bearing activity is positively associated with bone mineral density (BMD). Bone health in judoists and effects of weight cycling on bone metabolism have not previously been investigated. To examine potential disrupter and stimulators of bone integrity, this study analyzed bone parameters at baseline and the effects of the first weight cycle of the season on bone metabolic status in 48 male and female elite judoists.